2017
DOI: 10.4236/ojn.2017.74036
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Clinical Stressors among Saudi Nursing Students

Abstract: Purpose: Nursing profession is considered as a stressful and demanding job. The purpose of this research was to determine stressors types and degrees over two data collection periods in 2015-2016. Methods: This is a quantitative descriptive research study. A purposive sample of 55 female nursing students (complete 4 th year cohort) from Princess Nourah University took part in this study. Results: The results highlight that the most influential cause of stress were factors related to taking care of patients, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…There are many barriers to adherence to drug administration guidelines, including the failure to put evidence‐based research into practice, lack of support, poor communication among multidisciplinary teams and a working environment that does not support the culture of safety . In addition, nurses have reported that difficulty in reading handwritten orders, confusion about medications with similar names and lack of knowledge about patients’ medication allergies are contributory factors to MAEs .…”
Section: Introductionmentioning
confidence: 99%
“…There are many barriers to adherence to drug administration guidelines, including the failure to put evidence‐based research into practice, lack of support, poor communication among multidisciplinary teams and a working environment that does not support the culture of safety . In addition, nurses have reported that difficulty in reading handwritten orders, confusion about medications with similar names and lack of knowledge about patients’ medication allergies are contributory factors to MAEs .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the clinical requirements became a burden among nursing students (Galvin, Suominen, Morgan, O'Connell, & Smith, 2015). Assignment and clinical workloads were the perceived source of stress of the students in clinical training (Alsaqri, 2017;Hamaideh, Al-Omari, & Al-Modallal, 2017;Ismail, 2017). Due to this burden, students perceived the clinical training as merely complying with the paperwork requirements rather than honing their nursing skills.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, nursing students are educated to value communication, interaction and feedback as they are key concepts of patient care and safety. [12][13][14] The negative perception of communication via the LMS among our students may have compromised their learning and prevented them from achieving the course objectives. Therefore, to enhance self-directed learning through LMS use, it is essential to create an interactive learning environment.…”
Section: Discussionmentioning
confidence: 99%